International Monetary Fund Annual Report 1979. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1979)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1979. The report highlights that the performance of the world economy during 1978 and the first half of 1979 was characterized by a mixture of gains and disappointments. The evolution of domestic demand in several of the largest industrial countries proceeded broadly along the lines of a strategy of policy that had been agreed in various international forums. This development was beneficial to the distribution of external current account balances among individual countries within the industrial group.